CHARACTERISTIC OF SHALLOW-WATER TIDE COMPONENTS AND LONG- PERIOD TIDE COMPONENTS IN INDONESIA - Syella Angelina Manikape, Tiara
This Final Project examines the characteristics of shallow water tidal components and long period tidal components at the tidal stations of Sabang, Sibolga, Padang, Benoa, and Saumlaki. The data used is Research Quality Data in a span of one year in 2018, which was downloaded from the University of Hawaii Sea Level Center. The study analyzed the main tidal components (M2, S2, K1, and O1), 26 shallow tidal components and long-period tidal components (Ssa, Mm, Mf and Msf) using the T_TIDE data analysis method and the Fast Fourier Transform. Based on T_TIDE results, the significant shallow water component amplitudes 0,017 m (2N2), 0,014 m (M4), 0,018 m (M4), 0,011 m (MKS2), 0,019 m (2N2) at each tidal station of Sabang, Sibolga, Padang, Benoa, and Saumlaki. The significant long-period component is Ssa with amplitudes of 0,047 m, 0,052 m, 0,055 m, 0,054 m, 0,034 m at each tidal station of Sabang, Sibolga, Padang, Benoa, and Saumlaki. From the FFT results, the dominant tidal component in the entire study area has a period of 12 and 24 hours. Although small, short period (4 and 6 hours) and long period (15 to 30 days) components are still visible.